DEVELOPMENT OF AUGMENTED REALITY-BASED LEARNING MEDIA ON THE GEOMETRY OF SPACE FOR STUDENTS OF SMAN 6 PADANG - Amelia, Riska; Zuzano, Fazri (IJRDO- Journal of Educational Research, 2018)
This research aims to produce an Augmented Reality-based learning media with a valid, practical and effective shaped software (android application) that can display the geometry of space material on mathematical subjects. This type of research is R&D. on the research approach used is the development Model for the development of Four-D THIAGARAJAN. This research is done processed X SMAN 6 field. The stages in this study are Define, Design, Develop, and Disseminate. To find out the feasibility of the media used this learning instruments in the form of a review of media experts and expert material of product produced. Data collection techniques used are observation, interview and the study of librarianship. Augmented Reality method used in this research is a Markerless Augmented Reality with 3D Object Tracking techniques. Test results-based learning media functionality is Augmented Reality content geometry is done with black box testing with testing on some Android phones. Black box test showed that all functions on the AR Application geometry can function properly. The results of the expert assessment of the material and media experts stated that this application is valid for use. While the response assessment according to students based on ease of use, the effectiveness of the learning time, and the appeal of the merits gained 90.93% score.